Effect of low calcination temperature on the corrosion inhibition performance of biomass based Na2SiO3 on mild steel immersed in tap water. Issue 1 (31st December 2023) - Jembere, Addis Lemessa; Genet, Melkamu Birlie
Abstract: The present experimental study aimed at investigating the effect of certain calcination temperature zones on the corrosion prevention performance of biomass. Na2 SiO3 was synthesized from rice husk ash (RHA) calcined at 500°C, 550°C, and 600°C. The prepared RHA samples were characterized in terms of surface functional groups, chemical compositions, and crystallinity confirming the presence of the Si-O-Si (Silanol) group, an abundant constituent of SiO2, and the amorphous nature of the silica, respectively. The major step in the synthesis of Na2 SiO3 involves a reaction of sodium hydroxide with RHA (SiO2 ). The effect of inhibitor dose and immersion time on corrosion rate and inhibition efficiency was investigated on mild steel prepared strips. The interaction of the parameter that results in maximum corrosion efficiency of 95.41% was recorded at 30 ml of inhibition dose and 144 hours of immersion time in a sample prepared from 600°C calcined RHA. Isotherm study resulted in best fit on Temkin isotherm model for all samples, a kinetic model was best represented by pseudo-second-order for 500°C and 600°C thermally treated samples and pseudo-zero-order kinetic model for 550°C. The thermodynamic model revealed important parameters including activation energy, enthalpy, and entropy confirming the endothermic process, feasibility, and energy barrier formed on the metal surface. Generally, the effect of low-temperature extracted Na2 SiO3 showed a significant effect on the buildup of protective layer which is determined by the amount of silica content and reactivity.